STUDY LITERATUR:FAKTOR RESIKO YANG BERHUBUNGAN DENGAN KEJADIAN PNEUMONIA PADA BALITA - Ulfa Fadilla Dalimunthe; Susilawati (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
Pneumonia is one of the causes of high morbidity and mortality in children under five years old in developing countries, 19% of under-five deaths are caused by pneumonia. In 2022, the Ministry of Health has achieved the target in the treatment of pneumonia cases by 53% of the 50% target. The purpose of the study was to analyze what are the factors that influence the occurrence of pneumonia in toddlers. This research method uses the literature review method (litaratur riview) from several research results published from 2018 – 2022 and obtained 16,800 articles searched, obtained 4 articles that match the criteria. The results of the literature review are known that there is exclusive breastfeeding, working mothers, completeness of immunization including measles immunization, no relationship between low birth weight and pneumonia and nutritional status of infants &; male sex who are more susceptible to cases than women